Elements of Theatre of Absurd in Uzbek Literature - Xatamova, Nodiraxon Qosimjonqizi (Journal of Higher Education and Academic Advancement, 2024)
This article provides information about the theater of the absurd in Uzbek literature. The new theater phenomenon violated the traditional dramatic laws and did not recognize any authority.